2016
DOI: 10.1371/journal.pone.0146332
|View full text |Cite
|
Sign up to set email alerts
|

Six Year Refractive Change among White Children and Young Adults: Evidence for Significant Increase in Myopia among White UK Children

Abstract: ObjectiveTo determine six-year spherical refractive error change among white children and young adults in the UK and evaluate differences in refractive profiles between contemporary Australian children and historical UK data.DesignPopulation-based prospective study.ParticipantsThe Northern Ireland Childhood Errors of Refraction (NICER) study Phase 1 examined 1068 children in two cohorts aged 6–7 years and 12–13 years. Prospective data for six-year follow-up (Phase 3) are available for 212 12–13 year olds and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 44 publications
11
92
4
1
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26] According to the results of population-based studies using autorefraction, East Asian children appeared to have a higher incidence of myopia than Caucasian children. [13][14][15]17,18,[22][23][24] A 1-year longitudinal cohort study in Hong Kong revealed a mean annual incident rate of 14.41% among 3149 children aged between 5 and 16 years at baseline. 18 The annual incidence rates were reported by Saw et al 13 to be 15.9%, 12.8%, and 10.8% for 7-, 8-, and 9-year-old Singaporean children (n ¼ 569), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26] According to the results of population-based studies using autorefraction, East Asian children appeared to have a higher incidence of myopia than Caucasian children. [13][14][15]17,18,[22][23][24] A 1-year longitudinal cohort study in Hong Kong revealed a mean annual incident rate of 14.41% among 3149 children aged between 5 and 16 years at baseline. 18 The annual incidence rates were reported by Saw et al 13 to be 15.9%, 12.8%, and 10.8% for 7-, 8-, and 9-year-old Singaporean children (n ¼ 569), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Caucasian children were reported to have low and similar annual incidence of myopia in the United States (4.3% for 8-to 9-year-olds), 14 Australia (1.3% for 6-to 7-year-olds; 2.9% for 12-to 13-year-olds), 22 and the United Kingdom (2.2% for 6-to 7-year-olds; 0.7% for 12-to 13-year-olds). 23 Of interest, the annual incidence rates for the children of East Asian ethnicity living in the Sydney Metropolitan region (6.9% for 6-to 7-year-olds; 7.3% for 12-to 13-year-olds) 22 are comparable to those for rural populations of China and lower than those for children living in other metropolitan cities in East Asia, such as Hong Kong, Singapore, or Taipei, which indicates that environmental and lifestyle differences may play an important role in the development of childhood myopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 One in five teenagers are myopic in the UK. 3 Interventions shown to reduce myopia include atropine eye-drops, glasses (bifocal, varifocal, peripherally defocused) and lifestyle interventions such as increased exercise and time outdoors. 4 In this large interventional study, a school-based outdoor exercise programme reduced myopia by 9.5% and prevented 78 children from requiring glasses.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] Clear retinal images are implicated in normal emmetropisation, but if poor binocular vision causes sub-normal accommodation (as is also common in refractive error 33,[36][37][38][39][40][41][42] ), then it may impair emmetropisation due to increased blur for near, even when refractive error is corrected for distance. This is a possible direction for further study.…”
Section: Poor Convergence or Binocular Vision May Have Refractive Errmentioning
confidence: 99%